'Trade Union News for Overseas', 1955 (1955)
1955 1945-1960 "'Trade Union News for Overseas', 1955" [T0456.jpg], 1955 This article in the TUC bulletin 'Trade Union News for Overseas' of 6 July, 1955 is entitled 'How the TUC aids the colonies' and outlines an aid package for trade unions in the Caribbean area, in particular British Guiana and Trinidad.